Transitions and transformations in learning and education - Stenström, Marja-Leena; Saarnivaara, Marjatta; Tynjälä, Päivi (Springer Netherlands, 2012)
The breakneck speed of change in today's societies creates enormous challenges for educational institutions at all levels. This volume explores ways  how to manage change in educational processes and contexts,  focusing, in particular, on the concepts of transition and transformation. How do we educate a skilled workforce, sensitive professionals and responsive citizens who are able not only to cope with change but also to adopt required roles as agents of change? How do we prepare students and employees to cope adequately with changes and transitions in their careers and personal lives? The first of this book's three sections deals with the conceptual and theoretical aspects of transition, transformational processes and human development. It defines these concepts and examines the ways in which educational theory and praxis understand concepts of change and development. The second section presents empirical studies that offer differing perspectives on educational transitions, covering the lifespan from early years education to lifelong learning. The third part of the volume focuses on issues of learning and pedagogy and argues that educational practices should change with the changing world. With numerous concrete examples included in the analysis, and with studies taking a range of forms from personal histories to large-scale surveys, this new book is a major addition to the literature in a field that has key implications for our future.